DEVELOPMENT AND REGISTRATION OF A COMBINED DRUG FOR THE TREATMENT OF HIV INFECTION ON THE BASIS OF ON NUCLEOSIDE REVERSE TRANSCRIPTASE INHIBITORS (NRTI) PHOSPHAZIDE AND LAMIVUDINE - A. F. Khohlov; B. V. Brovchenko; A. A. Smirnov (Разработка и регистрация лекарственных средств, 2019)
The article discusses the development process of a combined medicinal product Phosphaladin® intended for the treatment of HIV infection, based on phosphazide and lamivudine. A brief review of epidemiological situation on HIV infection taking into account the import substitution policy in the pharmaceutical industry, as well as the problem of providing HIV-infected patients require therapy. Considers the issues of pharmaceutical development combined drug and preparation of preclinical and clinical units of the registration dossier.